Assessment of Psychological Well-Being among Elderly Individuals in Selected Community Areas of Vadodara District, Gujarat: A Cross- Sectional Study - Ms. Palak Patel; Dr. Ravindra H.N (The Bioscan, 2026)
Background: Population ageing is a global phenomenon, with a rapid increase in the proportion of elderly individuals, particularly in developing countries like India. Psychological well-being among the elderly has emerged as a critical public health concern, as ageing is often associated with increased vulnerability to mental health issues such as depression, anxiety, and reduced life satisfaction. Understanding these psychological dimensions is essential for designing community-based interventions that enhance quality of life in later years.